Household awareness and behaviour towards e-waste management systems in Shah Alam city / Nurul Ezaliya Husna Hussin, Nor Eeda Ali and Natasha Khalil - Hussin, Nurul Ezaliya Husna; Ali, Nor Eeda; Khalil, Natasha (2022)
E-waste management has become a concern in today's technology-based era, where electronic equipment is on the rise, complicating the transition to sustainable management. As more electronic equipment is developed to fulfill people's demands worldwide, more resources are allocated to its development. From 1981 to 2020, the amount of E-waste generated in Malaysia increased considerably, and this trend is likely to continue in the coming years. Many governments have been forced to adopt and enforce environmentally sustainable management in order to decrease health and environmental hazards, as well as to maximize the reuse, recycling, and recovery of precious e-waste resources. However, there are challenges that make government strategies more difficult to implement, which are household awareness and behaviour. Therefore, this paper aim to determine household awareness and behaviour toward e-waste management systems in Shah Alam city. A total of ten participants were recruited for the survey in January 2022 as a result of a screening form issued to households based on the criteria set. The study's findings revealed that household awareness and behaviour are the key problems complicating e-waste management in Shah Alam city. This study emphasizes the importance of supporting environmentally friendly practices and education on e-waste management that meet the demands of households as a strategy for long-term sustainability.